High-elastic polyester staple fiber oiling agent and application thereof
By using specific antistatic agents in high elastic polyester staple fiber oil agent, the problem of existing oil agents causing the fiber to feel hard, achieving both fiber resilience and softness.
Patent Information
- Application Number
- CN202411707044.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-07
AI Technical Summary
When the existing high-elastic polyester staple fiber oil agent improves the elasticity of the fiber, the fiber's elastic modulus is large, resulting in a hard feel.
Using a high elastic polyester staple fiber oil agent including a specific antistatic agent, the antistatic agent consists of C8-C18 alkyl groups and ethoxylated groups, by mixing the ratio of smoothing agent, bundling agent and antistatic agent, Improves the softness of the fiber.
The fiber resilience is achieved, while reducing the elastic modulus of the fiber, improving the softness and feel of the fiber.
Smart Images

Figure CN119392412A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a high-elastic polyester staple fiber oil agent and application thereof. Background Art
[0002] Due to its excellent physical properties and mature process development, polyester staple fiber has more and more diversified applications in the market, including automotive interior, home textiles, footwear materials, health care, construction, filtration, etc. With the improvement of people's living standards and the advancement of science and technology, the market has put forward more concrete requirements for the functional segmentation of products. For example, the field of home textiles alone can be subdivided into a variety of product series such as imitation fur, flame retardant, water repellent, high elasticity, and super smooth. In general, the above problems can be solved from three aspects: raw material modification, process equipment improvement, and surface treatment of textile auxiliaries. However, in order to adapt to the diversified switching of products in some chemical fiber plants, the surface treatment of fibers by textile auxiliaries has become a popular and flexible way with low cost.
[0003] High elastic polyester staple fiber oil is ordinary polyester staple fiber treated with oil to make the fiber have better resilience, meeting some needs of filling, saving materials, etc. The formula of this type of oil on the market is based on octadecyl dimethyl hydroxyethyl ammonium nitrate (commonly known as antistatic agent SN), but although antistatic agent SN improves the resilience of the fiber, the elastic modulus of the fiber is large, resulting in the defect of the fiber having a hard feel. Summary of the invention
[0004] One of the technical problems to be solved by the present invention is to provide a high-elastic polyester staple fiber oil agent, the polyester staple fibers produced by the oil agent have the advantages of good resilience and low elastic modulus.
[0005] To solve one of the above technical problems, the technical solution of the present invention is as follows:
[0006] A high-elastic polyester staple fiber oil agent, comprising the following components by weight:
[0007] Smoothing agent, 10-70 parts;
[0008] Clustering agent, 5 to 30 parts;
[0009] Antistatic agent, 10-40 parts;
[0010] The antistatic agent includes a substance that conforms to the following formula 1:
[0011]
[0012] R1 is a C8-C18 alkyl group, for example but not limited to, R1 is a C8 alkyl group, a C9 alkyl group, a C10 alkyl group, a C11 alkyl group, a C12 alkyl group, a C13 alkyl group, a C14 alkyl group, a C15 alkyl group, a C16 alkyl group, a C17 alkyl group or a C18 alkyl group;
[0013] R2 is an ethoxylated group, and the structural formula is:
[0014] -(CH2CH2O) m H, formula 2;
[0015] R3 is an ethoxylated group, and the structural formula is:
[0016] -(CH2CH2O) p H, formula 3;
[0017] R4 is an ethoxylated group, and the structural formula is:
[0018] -(CH2CH2O) q H, formula 4;
[0019] Wherein, the product of m, p and q is greater than 0, and the sum of m, p and q is 3 to 30, for example but not limited to, the sum of m, p and q is 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 20, 25, etc.;
[0020] X is an anion or anionic group, and n is the charge number of X.
[0021] The oil of the present invention has the advantages of good resilience and low elastic modulus of polyester staple fibers produced by the oil. The technical key of the present invention is to use an antistatic agent shown in Formula 1, which improves the softness of the fibers in the oil of the present invention.
[0022] By way of non-limiting example, the smoothing agent is 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, 35 parts, 40 parts, 45 parts, 50 parts, 55 parts, 60 parts, 65 parts, 70 parts, and the like.
[0023] By way of non-limiting example, the sizing agent is 5 parts, 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, and so on.
[0024] By way of non-limiting example, the antistatic agent is present in 10, 15, 20, 25, 30, 35, 40 parts, etc.
[0025] For example but not limited to, X is Cl, Br, SO4, CH3OSO3, CH3CH2OSO3, CH3COO, NO3, etc.
[0026] In the above technical solution, the oil agent preferably includes an oxide of a fatty amine ethoxylated group, referred to as oxide A, wherein oxide A conforms to formula 5:
[0027]
[0028] R5 is a C8-C18 alkyl group, for example but not limited to, R5 is a C8 alkyl group, a C9 alkyl group, a C10 alkyl group, a C11 alkyl group, a C12 alkyl group, a C13 alkyl group, a C14 alkyl group, a C15 alkyl group, a C16 alkyl group, a C17 alkyl group or a C18 alkyl group;
[0029] R6 is an ethoxylated group shown in Formula 6:
[0030] -(CH2CH2O) r H, formula 6,
[0031] R7 is an ethoxylated group shown in Formula 7:
[0032] -(CH2CH2O) s H, formula 7,
[0033] Among them, the product of r and s is greater than 0, and the sum of r and s is 2-20, for example but not limited to, the sum of r and s is 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, etc.
[0034] Oxide A has a synergistic effect on the antistatic agent described in Formula 1 in terms of improving the softness of the fiber.
[0035] In the above scheme, the mass ratio of oxide A to the antistatic agent is preferably 0.01 to 0.3, for example but not limited to 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, 0.25, etc.
[0036] In the above technical solution, the smoothing agent is not particularly limited, for example, the smoothing agent may include at least one selected from the group consisting of fatty alcohol polyoxyethylene ethers (such as but not limited to peregal) and polyol esters (such as but not limited to fatty acid glycerides). For comparison only, peregal O-60, i.e., cetostearyl alcohol polyoxyethylene (60) ether, is generally used in the specific embodiments of the present invention.
[0037] In the above technical solution, the sizing agent is not particularly limited, and can be, for example, at least one of alkylphenol polyoxyethylene ether and fatty acid polyoxyethylene ester. For example, saturated fatty acid polyoxyethylene ester and / or unsaturated fatty acid polyoxyethylene ester. For comparison only, the specific embodiment of the present invention generally adopts stearic acid polyoxyethylene (9) ester.
[0038] In the above technical solution, the oil agent may include a solvent.
[0039] In the above technical solution, it is preferred that the solvent mainly contains water. It is easy for those skilled in the art to understand that mainly containing water means that the weight content of water in the solvent is greater than 50%, for example but not limited to the weight content of water in the solvent is 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95% or 100%, etc.
[0040] In the above technical solution, the solvent preferably includes water and a water-soluble organic solvent. For example, but not limited to, the water-soluble organic solvent is acetone, ethanol, isopropanol, etc. In most cases, the above-mentioned water-soluble organic solvent is usually a raw material purchased from a commercial channel, and is sometimes supplied in the form of a solution, and a water-soluble organic solvent is sometimes used in the solvent of these solutions.
[0041] The use of solvents in the formula allows the various component monomers of the oil agent to be evenly mixed and maintain a flowing liquid state at room temperature for easy use. Apart from this, no significant effect on the properties of the fiber was found.
[0042] In order to facilitate storage and on-site dilution, it is preferred that the mass content of the solvent in the oil is 20-90% (for example but not limited to 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85% and the like); or the mass concentration of the effective substance in the oil is 10-80% (for example but not limited to 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75% and the like).
[0043] In order to facilitate the on-site oiling of the fibers, the oil used is in the form of an oil emulsion, in which the mass content of the solvent is 92.0-99.8% (for example, but not limited to 93%, 94%, 95%, 96%, 97%, 98%, 99%, 99.5%, 99.8%, etc.); or the mass content of the oil effective substance in the oil emulsion is 0.2-8.0% (for example, but not limited to 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, etc.).
[0044] The effective substances in the oil are the general term for the components other than the solvent in the oil.
[0045] The technical key of the oil of the present invention is the selection of the various components in the above oil. As for the preparation method, it can be understood by those skilled in the art that the various components required for the oil are mixed evenly without the need for creative labor.
[0046] For example, but not limited to, the preparation method of the oil agent includes the following steps:
[0047] Add measured solvent into the mixing kettle and heat it to 60-80°C;
[0048] Start stirring, add the effective components or solutions of the effective components required by the formula, stir evenly at 60-80°C, cool to 25-40°C and discharge.
[0049] The second technical problem to be solved by the present invention is the application of the oil agent, and the technical solution is:
[0050] The use of any one of the oil agents described in the technical solution of one of the above technical problems in the production of high-elastic polyester staple fibers.
[0051] The technical key of the present invention is the selection of the oil component. As for the specific process conditions used in the production of polyester staple fibers, those skilled in the art can make reasonable selections without having to make creative efforts.
[0052] Just as an example, the production of polyester staple fiber is divided into pre-spinning and post-spinning. Pre-spinning generally uses post-spinning reflux oil emulsion with a lower concentration; post-spinning can use two-step oiling methods, oil tank immersion padding and curling spraying, or oil tank immersion padding. The concentration of oil emulsion in the post-spinning area is higher than that in the pre-spinning area, which determines the oiling effect of the fiber. It is necessary to maintain a relatively constant concentration of oil emulsion. The fiber is cut and packaged after drying. The oil content of polyester staple fiber is controlled to be 0.10% to 0.25% according to the fiber thickness specifications and customer requirements.
[0053] The substance shown in Formula 1 can be obtained from commercial channels, such as decyl triethanolammonium bromide (CAS 60535-39-9), etc., or can be easily obtained according to existing synthesis technology. The substance shown in Formula 1 is obtained by quaternization reaction of triethanolamine or triethanolamine polyoxyethylene ether with alkyl halide; for example, "CN102643204A_Trihydroxyethyl quaternary ammonium salt and preparation method thereof" discloses this method, and "CN102079713A_Crosslinkable polymerized quaternary ammonium salt type antibacterial monomer and preparation method thereof and application in dental restoration materials" discloses this method in multiple places, such as paragraphs
[0044] ,
[0067] and
[0079] of the specification. It can also be obtained by quaternizing N-alkyldiethanolamine with halogenated ethanol in the presence of an alkali metal hydroxide (Wang Jun et al. Study on the physicochemical properties of N-dodecyl-N,N,N-trihydroxyethylammonium chloride. Chemical World [J], Issue 11, 2022: 595-598). For comparison only, the substance shown in Formula 1 used in the specific embodiment of the present invention takes octadecyltrihydroxyethylammonium bromide as an example.
[0054] The octadecyl trihydroxyethyl ammonium bromide used in the present invention is synthesized according to CN102079713A, specifically as follows:
[0055] In 1000 ml of acetone, add 1 mol of triethanolamine and 1 mol of 1-bromooctadecane, reflux for 24 hours, then cool to room temperature, filter and dry to obtain the target product.
[0056] The oxide of the fatty amine ethoxylate shown in Formula 5 can be easily obtained from commercial channels, such as dodecyl dihydroxyethylamine oxide (CAS 2530-44-1) and octadecyl dihydroxyethylamine oxide (CAS 61791-46-6), or can be obtained by using mature existing technology - using hydrogen peroxide to oxidize N-alkyl diethanolamine, or using hydrogen peroxide to oxidize fatty amine polyoxyethylene ether. For comparison only, in the specific embodiment of the present invention, a commercially available octadecyl dihydroxyethylamine oxide aqueous solution with a mass concentration of 25% is used as the source of octadecyl dihydroxyethylamine oxide.
[0057] Testing of the Invention
[0058] The test of the present invention needs to be characterized by testing various indicators of the treated fiber sample after the fiber is oiled, as follows:
[0059] 1. Preparation of fiber samples
[0060] The white polyester staple fiber with a specification of 6D×51mm produced by Jiangyin Dazhongyuan Special Chemical Fiber Co., Ltd. was first washed with pure water for 4 times, and then ultrasonically cleaned with ethanol for 5 minutes to remove impurities such as dust and grease on the surface. The fiber was taken out and dried in a blast drying oven at 40°C, and then placed in a constant temperature and humidity chamber at a temperature of 25°C and a relative humidity of 65%RH for more than 24 hours as a fiber standby sample.
[0061] Prepare the oil into an oil-water emulsion with an effective mass concentration of 0.20% as the test liquid. Weigh several grams of fiber sample, soak it in the above oil emulsion at 60℃ for 60s, take it out and spin dry it, then dry it in a blast drying oven at 110℃ to constant weight to obtain the treated fiber sample. Place it in a constant temperature and humidity environment of 25℃ and 65%RH for testing.
[0062] 2. Fiber testing
[0063] 2.1 Fiber elastic modulus
[0064] The initial elastic modulus of the fiber is tested in dry state according to GB / T 14337-2022 "Test method for tensile properties of chemical fibers-short fibers". The larger the initial elastic modulus of the fiber, the harder the fabric feels; conversely, the softer the fabric feels.
[0065] 2.2 Fiber Elasticity
[0066] Fiber elasticity refers to the ability of a certain fiber to recover its volume after the specified load is removed. The H value of the sample is tested according to method A in the industry standard FZ / T50009.4-2019 Test method for bulkiness and elasticity of hollow polyester staple fibers. Each test accurately weighs 100±0.5 grams of the sample, and the test result is expressed as the average value of three samples, rounded to an integer. The larger the H value, the stronger the fiber's recovery force after the load is removed, and the better the fiber's resilience.
[0067] 2.3 Volume resistivity of fibers
[0068] The volume resistivity was measured using a MR-2010 resistor meter and its resistivity was calculated using formula 1.
[0069] Specific resistance value ρ = 12 × R × f (Formula 1)
[0070] Where: R represents the measured resistance
[0071] f represents the standard filling degree of the material, and the standard filling degree value of polyester is 0.23.
[0072] 2.4 Friction coefficient
[0073] The friction coefficient of yarn was measured using the Y151 yarn friction coefficient tester produced by Changzhou Second Textile Machinery Plant.
[0074] The test speed of the friction coefficient tester was set to 50 rpm and the wrap angle was set to 180°, and the dynamic friction coefficient (μd) and static friction coefficient (μs) of the test fiber were measured.
[0075] a) Determination of static friction coefficient
[0076] Using a stainless steel roller as the roller core, the fiber sample in step 1 is made into a fiber roller to complete the work to be tested.
[0077] Take the sample fiber, clamp a tension clamp (20mg) at each end, hang one on the torsion balance hook, and hang the other on the fiber roller. Turn the transmission belt toward the torsion balance hook to make the pointer deflect to the right, then turn the handle. When the pointer of the balance tends to deflect from right to left, record the reading on the torsion balance at this time. Turn the handle to reset it, and take the average value after three measurements for each group. Take the average value after three tests and look up the table.
[0078] b) Determination of dynamic friction coefficient
[0079] The method of making the fiber roller is the same as that of measuring the static friction coefficient. Turn on the friction coefficient meter, rotate the fiber roller at a speed of 50 rpm, slowly turn the balance handle until the balance pointer swings left and right at the same amplitude in the equilibrium position, record the reading on the torsion balance at this time, and take the average value after three measurements for each group. After testing three groups, take the average value and look up the table.
[0080] According to experience, for oil-containing fibers, the static friction coefficient μs between fibers is preferably between 0.25 and 0.35, the dynamic friction coefficient μd between fibers is preferably between 0.15 and 0.26, and the volume resistivity of the fibers is preferably less than 10 8 Ω·cm can meet the spinning requirements. The lower the volume resistivity of the fiber, the better the antistatic property of the oil agent, which is more beneficial to the fiber production and downstream processing.
[0081] The present invention is described in detail below through specific implementation modes. DETAILED DESCRIPTION
[0082] [Comparative Example 1]
[0083] 1. Oil formulation with 40% active substance concentration
[0084] Substances other than solvents are calculated as effective substances:
[0085]
[0086] 2. Oil preparation
[0087] (1) Add 100 parts by weight of water into a mixing kettle;
[0088] (2) Start stirring, control the kettle temperature to 70° C., then add 45 parts by weight of Periga O-60 and 15 parts by weight of polyoxyethylene (9) stearate and stir for 30 minutes;
[0089] (3) adding 40 parts by weight of SN solution (containing 20% isopropanol, 15% ethanol and 15% water) with an effective substance concentration of 50% at 70° C. and continuing stirring at the same temperature for 60 minutes;
[0090] (4) Cool down to 30°C and discharge the material to obtain the finished oil product.
[0091] 3. Oil performance test
[0092] After testing, the elastic modulus is 4.39cN / dtex, the fiber elasticity H is 67%, and the volume resistivity is 7.9*10 7 Ω·cm, the static friction coefficient is 0.309, and the dynamic friction coefficient is 0.221.
[0093] [Comparative Example 2]
[0094] 1. Oil formulation with 40% active substance concentration
[0095] Substances other than solvents are calculated as effective substances:
[0096]
[0097] 2. Oil preparation
[0098] (1) Add 60 parts by weight of water into a mixing kettle;
[0099] (2) Start stirring, control the kettle temperature to 70° C., then add 45 parts by weight of Periga O-60 and 15 parts by weight of polyoxyethylene (9) stearate and stir for 30 minutes;
[0100] (3) adding 80 parts by weight of an aqueous solution of octadecyl dihydroxyethyl amine oxide having an effective mass concentration of 25% at 70° C. and continuing stirring at the same temperature for 60 minutes;
[0101] (4) Cool down to 30°C and discharge the material to obtain the finished oil product.
[0102] 3. Oil performance test
[0103] After testing, the elastic modulus is 4.18cN / dtex, the fiber elasticity H is 62%, and the volume resistivity is 3.2*10 7 Ω·cm, the static friction coefficient is 0.299, and the dynamic friction coefficient is 0.224.
[0104] [Comparative Example 3]
[0105] 1. Oil formulation with 40% active substance concentration
[0106] Substances other than solvents are calculated as effective substances:
[0107]
[0108] In the formula, the CAS number of the antistatic agent TM is 29463-06-7, and its Chinese name is trihydroxyethyl methyl quaternary ammonium methyl sulfate.
[0109] 2. Oil preparation
[0110] (1) Add 120 parts by weight of water into a mixing kettle;
[0111] (2) Start stirring, control the kettle temperature to 70° C., then add 45 parts by weight of Periga O-60 and 15 parts by weight of polyoxyethylene (9) stearate and stir for 30 minutes;
[0112] (3) adding 20 parts by weight of antistatic agent TM at 70° C. and continuing stirring at the same temperature for 60 minutes;
[0113] (4) Cool down to 30°C and discharge the material to obtain the finished oil product.
[0114] 3. Oil performance test
[0115] After testing, the elastic modulus is 4.57cN / dtex, the fiber elasticity H is 59%, and the volume resistivity is 6.6*10 6 Ω·cm, the static friction coefficient is 0.316, and the dynamic friction coefficient is 0.217.
[0116] [Example 1]
[0117] 1. Oil formulation with 40% active substance concentration
[0118] Substances other than solvents are calculated as effective substances:
[0119]
[0120] 2. Oil preparation
[0121] (1) Add 120 parts by weight of water into a mixing kettle;
[0122] (2) Start stirring, control the kettle temperature to 70° C., then add 45 parts by weight of Periga O-60 and 15 parts by weight of polyoxyethylene (9) stearate and stir for 30 minutes;
[0123] (3) adding 20 parts by weight of octadecyl tris(hydroxyethyl) ammonium bromide at 70° C. and continuing stirring at the same temperature for 60 minutes;
[0124] (4) Cool down to 30°C and discharge the material to obtain the finished oil product.
[0125] 3. Oil performance test
[0126] After testing, the elastic modulus is 3.51cN / dtex, the fiber elasticity H is 73%, and the volume resistivity is 2.1*10 7 Ω·cm, the static friction coefficient is 0.286, and the dynamic friction coefficient is 0.206.
[0127] [Example 2]
[0128] 2. Oil formulation with 40% active substance concentration
[0129] Substances other than solvents are calculated as effective substances:
[0130]
[0131] 2. Oil preparation
[0132] (1) Add 111 parts by weight of water into a mixing kettle;
[0133] (2) Start stirring, control the kettle temperature to 70° C., then add 45 parts by weight of Periga O-60 and 15 parts by weight of polyoxyethylene (9) stearate and stir for 30 minutes;
[0134] (3) adding 12 parts by weight of an aqueous solution of octadecyl dihydroxyethyl amine oxide having an effective mass concentration of 25% and 17 parts by weight of octadecyl trihydroxyethyl ammonium bromide at 70° C.; and continuing stirring at the same temperature for 60 minutes;
[0135] (4) Cool down to 30°C and discharge the material to obtain the finished oil product.
[0136] 3. Oil performance test
[0137] After testing, the elastic modulus is 3.23cN / dtex, the fiber elasticity H is 71%, and the volume resistivity is 7.4*10 6 Ω·cm, the static friction coefficient is 0.283, and the dynamic friction coefficient is 0.195.
[0138] [Comparative Example 4]
[0139] 1. Oil formulation with 40% active substance concentration
[0140] Substances other than solvents are calculated as effective substances:
[0141]
[0142] 2. Oil preparation
[0143] (1) Add 94 parts by weight of water into a mixing kettle;
[0144] (2) Start stirring, control the kettle temperature to 70° C., then add 45 parts by weight of Periga O-60 and 15 parts by weight of polyoxyethylene (9) stearate and stir for 30 minutes;
[0145] (3) adding 12 parts by weight of an aqueous solution of octadecyl dihydroxyethyl amine oxide having an effective mass concentration of 25% and 34 parts by weight of an octadecyl dimethyl hydroxyethyl ammonium nitrate (SN) solution having an effective mass concentration of 50% (containing 20% isopropanol, 15% ethanol and 15% water) at 70° C.; and continuing stirring at the same temperature for 60 minutes;
[0146] (4) Cool down to 30°C and discharge the material to obtain the finished oil product.
[0147] 3. Oil performance test
[0148] After testing, the elastic modulus is 4.26cN / dtex, the fiber elasticity H is 64%, and the volume resistivity is 5.2*10 7 Ω·cm, the static friction coefficient is 0.301, and the dynamic friction coefficient is 0.259.
[0149] [Comparative Example 5]
[0150] 1. Oil formulation with 40% active substance concentration
[0151] Substances other than solvents are calculated as effective substances:
[0152]
[0153] In the formula, the CAS number of the antistatic agent TM is 29463-06-7, and its Chinese name is trihydroxyethyl methyl quaternary ammonium methyl sulfate.
[0154] 2. Oil preparation
[0155] (1) Add 111 parts by weight of water into a mixing kettle;
[0156] (2) Start stirring, control the kettle temperature to 70° C., then add 45 parts by weight of Periga O-60 and 15 parts by weight of polyoxyethylene (9) stearate and stir for 30 minutes;
[0157] (3) adding 12 parts by weight of an aqueous solution of octadecyl dihydroxyethyl amine oxide having an effective mass concentration of 25% and 17 parts by weight of an antistatic agent TM at 70° C.; and continuing stirring at the same temperature for 60 minutes;
[0158] (4) Cool down to 30°C and discharge the material to obtain the finished oil product.
[0159] 3. Oil performance test
[0160] After testing, the elastic modulus is 4.30cN / dtex, the fiber elasticity H is 58%, and the volume resistivity is 9.4*10 6 Ω·cm, the static friction coefficient is 0.313, and the dynamic friction coefficient is 0.247.
[0161] [Example 3]
[0162] 1. Oil formulation with 40% active substance concentration
[0163] Substances other than solvents are calculated as effective substances:
[0164]
[0165]
[0166] 2. Oil preparation
[0167] (1) Add 114 parts by weight of water into a mixing kettle;
[0168] (2) Start stirring, control the kettle temperature to 70° C., then add 45 parts by weight of Periga O-60 and 15 parts by weight of polyoxyethylene (9) stearate and stir for 30 minutes;
[0169] (3) adding 8 parts by weight of an aqueous solution of octadecyl dihydroxyethyl amine oxide having an effective mass concentration of 25% and 18 parts by weight of octadecyl trihydroxyethyl ammonium bromide at 70° C.; and continuing stirring at the same temperature for 60 minutes;
[0170] (4) Cool down to 30°C and discharge the material to obtain the finished oil product.
[0171] 3. Oil performance test
[0172] After testing, the elastic modulus is 3.42cN / dtex, the fiber elasticity H is 68%, and the volume resistivity is 1.7*10 7 Ω·cm, the static friction coefficient is 0.289, and the dynamic friction coefficient is 0.211.
[0173] [Example 4]
[0174] 1. Oil formulation with 40% active substance concentration
[0175] Substances other than solvents are calculated as effective substances:
[0176]
[0177] 2. Oil preparation
[0178] (1) Add 108 parts by weight of water into a mixing kettle;
[0179] (2) Start stirring, control the kettle temperature to 70° C., then add 45 parts by weight of Periga O-60 and 15 parts by weight of polyoxyethylene (9) stearate and stir for 30 minutes;
[0180] (3) adding 16 parts by weight of an aqueous solution of octadecyl dihydroxyethyl amine oxide having an effective mass concentration of 25% and 16 parts by weight of octadecyl trihydroxyethyl ammonium bromide at 70° C.; and continuing stirring at the same temperature for 60 minutes;
[0181] (4) Cool down to 30°C and discharge the material to obtain the finished oil product.
[0182] 3. Oil performance test
[0183] After testing, the elastic modulus is 3.45cN / dtex, the fiber elasticity H is 69%, and the volume resistivity is 8.9*10 6 Ω·cm, the static friction coefficient is 0.295, and the dynamic friction coefficient is 0.208.
Claims
1. A high-elastic polyester staple fiber oil agent, comprising the following components by weight: Smoothing agent, 10-70 parts; Clustering agent, 5 to 30 parts; Antistatic agent, 10-40 parts; Its characteristics are The antistatic agent includes a substance that conforms to the following formula 1: R1 is a C8-C18 alkyl group; R2 is an ethoxylated group, and the structural formula is: -(CH2CH2O) m H, formula 2; R3 is an ethoxylated group, and the structural formula is: -(CH2CH2O) p H, formula 3; R4 is an ethoxylated group, and the structural formula is: -(CH2CH2O) q H, formula 4; Wherein, the product of m, p and q is greater than 0, and the sum of m, p and q is 3 to 30; X is an anion or an anionic group, and n is the charge number of X.
2. The oil according to claim 1, characterized in that include: Oxides of fatty amine ethoxylated groups, referred to as oxides A, wherein: Oxide A conforms to formula 5: R5 is a C8-C18 alkyl group; R6 is an ethoxylated group shown in Formula 6: -(CH2CH2O) r H, formula 6, R7 is an ethoxylated group shown in Formula 7: -(CH2CH2O) s H, formula 7, Among them, the product of r and s is greater than 0, and the sum of r and s is 2 to 20.
3. The oil according to claim 2, characterized in that The mass ratio of oxide A to the antistatic agent is 0.01 to 0.
3.
4. The oil according to claim 1, characterized in that The smoothing agent includes at least one selected from the group consisting of fatty alcohol polyoxyethylene ether (such as but not limited to peregal) and polyol ester (such as but not limited to fatty acid glyceride).
5. The oil according to claim 1, characterized in that The sizing agent is at least one of alkylphenol polyoxyethylene ether and fatty acid polyoxyethylene ester, such as saturated fatty acid polyoxyethylene ester and / or unsaturated fatty acid polyoxyethylene ester.
6. The oil according to claim 1, characterized in that The oil agent includes a solvent, and preferably the solvent mainly contains water.
7. The oil according to claim 6, characterized in that The water-soluble organic solvents include water and water-soluble organic solvents, such as acetone, ethanol, isopropanol, etc.
8. The oil according to claim 6, characterized in that In the oil, the mass content of the solvent is 20 to 90%; or the mass concentration of the effective substance in the oil is 10 to 80%.
9. The oil according to claim 8, characterized in that The mass content of the solvent in the oil emulsion which is convenient for direct use at the use site is 92.0-99.8%, or the mass content of the oil effective substance in the oil emulsion is 0.2-8.0%.
10. Use of the oil according to any one of claims 1 to 9 in the production of high-elastic polyester staple fibers.
Citation Information
Patent Citations
Cross-linked polyquaternary ammonium salt type antibiosis monomer, preparation method of cross-linked polyquaternary ammonium salt type antibiosis monomer and application of cross-linked polyquaternary ammonium salt type antibiosis monomer in dentistry repairing materials
CN102079713A
Trihydroxyethyl quaternary ammonium salt and preparation method thereof
CN102643204A